The PENGARUH E-SERVICE QUALITY, ONLINE CUSTOMER RATING DAN PRICE CONSCIOUSNESS TERHADAP REPURCHASE INTENTION PADA PENGGUNA SHOPEEFOOD DI KOTA SURAKARTA - Dini Muthi’ah Putri; Ari Susanti (Jurnal Riset Ilmu Ekonomi, 2023)
In the current era, digital start-ups are growing, and one of the most frequently used in everyday life is an application that provides food delivery services. ShopeeFood, which has just started operating in 2020, is strongly suspected of expanding its competitors that have long been operating in Indonesia. The purpose of this study is to explore further the extent to which people's interest in ShopeeFood is to prove whether the quality of electronic services, online customer ratings and price selection tendencies, price consciousness has an influence on repurchase intention. This study used a purposive sampling method which was limited by several criteria with a total sample of 113 respondents who had used ShopeeFood at least once, were at least 17 years old, and domiciled in Surakarta City, Central Java. The results obtained in this study indicate that price awareness has a significant effect on repurchase intention, while e-service quality and online customer ratings have no significant effect on repurchase intention.